The spatial implications of urban renewal carried out by the ECC programs in Pécs - Trócsányi, András (Hungarian Geographical Bulletin, 2011)
Cultural economy – interpreted in the broadest sense – is a phenomenon existing among the impacts of post-industrial transformation and renewal of cities. In this paper the changing and developing role of investments related to European Capital of Culture 2010 is tackled in a city, which used to have a commercial profile, later on it became an industrial centre and has recently provoked sharp debates on the further direction to follow in the frame of post-socialist economic and urban restructuring. Current tendencies and deliberate investment directions proceed towards significantly influencing the development of the city of Pécs in general and shaping its inner structure in particular.